Diastereodivergent Catalysis Using Modularly Designed Organocatalysts: Synthesis of both cis‐ and trans‐Fused Pyrano[2, 3‐b]pyrans. (6th January 2016) - Huang, Huicai; Konda, Swapna; Zhao, John C.‐G.
Abstract: Both enantiomers of cis ‐ and trans ‐fused 3, 4, 4a, 8a‐tetrahydro‐2H, 5H‐pyrano[2, 3‐b]pyran‐7‐carboxylates have been obtained in high diastereoselectivities and enantioselectivities from the same starting materials using a tandem inverse‐electron‐demand hetero‐Diels–Alder/oxa‐Michael reaction catalyzed by modularly designed organocatalysts (MDOs). Diastereodivergence was achieved in these reactions through the direct control of the stereochemistry of the bridgehead atoms of the fused ring using new MDOs self‐assembled from both enantiomers of proline and cinchona alkaloid thiourea derivatives.